PEMBINAAN DISIPLIN SANTRI PROGRAM TAFAQQUH PONDOK PESANTREN AL-BAHJAH CILIMUS - Az Zahro, Fatimah; Kulsum; Fadilah, Syifa Nurul; Salsabila, Dida Wardatus (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2023)
This study aims to describe the discipline development of Tafaqquh program students at Al-Bahjah Islamic Boarding School in Cilimus. The type of approach in this research is a qualitative approach with descriptive research. The data and data sources used are primary data and secondary data. The data sources in this study are 1) coordinator, 2) teaching staff, and 3) students. Data collection techniques with non-participant observation and structured interviews. Interviews were conducted with the Cilimus branch coordinator, teaching staff, and students. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of this study are the type of discipline coaching applied to the Tafaqquh program at Al-Bahjah Islamic Boarding School in Cilimus is authoritarian and free and controlled which makes students bound to existing rules but still given freedom with specified limits. Discipline coaching techniques are carried out through external control where coaches and administrators emphasize discipline continuously. This slowly fosters santri awareness of discipline. The punishment given is based on violation points which are calculated every day and the type of punishment educates the students. Factors that influence santri discipline include punishment, rewards, the environment, and the example of a teacher who is highly respected by them. The discipline development of students in the tafaqquh program of Al-Bahjah Islamic Boarding School runs and is well managed so that it can raise awareness in students to be disciplined.